Assessing the Effects of Knowledge, Taxpayer Awareness, Tax Amnesty, and Socialization on Motor Vehicle Tax Compliance - Ni Putu Ayu Satya Suciantari; Ni Luh Supadmi (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2024)
Tax compliance is defined as the extent of adherence exhibited by an individual or entity in paying taxes in accordance with applicable laws. This study aims to investigate the effects of knowledge, taxpayer awareness, tax amnesty programs (referred to as tax bleaching programs), and outreach efforts on the level of motor vehicle taxpayer compliance in Badung Regency. The theoretical frameworks of attribution theory and planned behavior theory underpin this research. Conducted at the Badung Regency SAMSAT Office, the study sampled 100 respondents using the accidental sampling method, derived via the Slovin formula. Data collection was performed through the distribution of questionnaires, followed by analysis using multiple linear regression. The findings indicate that taxpayer knowledge, tax amnesty programs, taxpayer awareness, and tax socialization significantly influence the level of compliance with motor vehicle tax (PKB) obligations.